2015
DOI: 10.1021/acs.inorgchem.5b00856
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Mechanism of Monometallic Rhodium Hydride Complexes

Abstract: The reduction of O2 to H2O mediated by a series of electronically varied rhodium hydride complexes of the form cis,trans-Rh(III)Cl2H(CNAd)(P(4-X-C6H4)3)2 (2) (CNAd = 1-adamantylisocyanide; X = F (2a), Cl (2b), Me (2c), OMe (2d)) was examined through synthetic and kinetic studies. Rhodium(III) hydride 2 reacts with O2 to afford H2O with concomitant generation of trans-Rh(III)Cl3(CNAd)(P(4-X-C6H4)3)2 (3). Kinetic studies of the reaction of the hydride complex 2 with O2 in the presence of HCl revealed a two-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Whilst it is mainly studied in palladium hydrides, 39,40 some research has been directed towards rhodium hydrides. 43 Our calculated energy barriers for this step can readily be overcome under the typical reaction conditions of 110 1C to 170 1C; a barrier of 0.65 eV is observed. For Rh(CO), a higher, yet still reasonable, barrier of 1.22 eV is calculated.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Whilst it is mainly studied in palladium hydrides, 39,40 some research has been directed towards rhodium hydrides. 43 Our calculated energy barriers for this step can readily be overcome under the typical reaction conditions of 110 1C to 170 1C; a barrier of 0.65 eV is observed. For Rh(CO), a higher, yet still reasonable, barrier of 1.22 eV is calculated.…”
Section: Resultsmentioning
confidence: 74%
“…This result is akin to the findings for the respective oxygen covered metal surface systems, where it was found that methane activates preferentially through a surface stabilised mechanism on Rh(111) and an oxygen promoted mechanism on Cu(111). 42,43 Despite this, the barrier observed for a metal oxo species remains moderately reasonable, therefore we must consider the facility of the formation of a rhodium metal oxo species. For the Cu-zeolite system, oxidation of the copper centre is understood as being the rate determining step, 44 and therefore, we computed the thermodynamic favourability of forming a RhQO species with respect to CuQO formation.…”
Section: Resultsmentioning
confidence: 99%
“…Here the operation of HAA and HXRE as competitive pathways to generate metal-hydoperoxo species was proposed. 44,49 The intermediacy of the dinuclear rhodium-hydroperoxo species was also supported by isolation of the related iridium complex, Ir 2 II,II (tfepma) 2 (CN t Bu) 2 Cl 3 (OOH), that was formed from Ir 2 II,II (tfepma) 2 (CN t Bu) 2 Cl 3 (H) and oxygen. 43 In Path D, oxygen undergoes oxidation addition at the metal and then a recombination/reductive elimination step to produce the metal-hydroperoxo product.…”
Section: ■ Introductionmentioning
confidence: 88%
“…In addition, Nocera and co-workers reported that the reduction of O 2 by Rh 2 II,II (tfepma) 2 (CN t Bu) 2 Cl 3 (H) (tfepma = MeN­[P­(OCH 2 CF 3 ) 2 ] 2 ) or cis , trans -Rh III Cl 2 H­(CNAd)­(P­(4-X-C 6 H 4 ) 3 ) 2 (CNAd = 1-adamantylisocyanide, X = F, Cl, Me, or OMe) proceeds with a two-term rate law. Here the operation of HAA and HXRE as competitive pathways to generate metal-hydoperoxo species was proposed. , The intermediacy of the dinuclear rhodium-hydroperoxo species was also supported by isolation of the related iridium complex, Ir 2 II,II (tfepma) 2 (CN t Bu) 2 Cl 3 (OOH), that was formed from Ir 2 II,II (tfepma) 2 (CN t Bu) 2 Cl 3 (H) and oxygen …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation